Pengaruh City Branding terhadap Image Of Urban Destination dan Dampaknya pada Post-Visit Behavior - Juanim J; Neng Lilis Rahmawati (TRIKONOMIKA, 2015)
The purpose of this study is to know the phenomenon and get empirical evidence, and also conclusion about the influence of city branding on image of urban destination and it impact on post-visit tourist behavior to Bandung city. This research using descriptive and verificative methods. The sampling technique is sampling incidental. The research surveyed 100 respondents. Data analysis method of this research using path analysis. The result of this reveals that, City branding of Bandung as a creative city in the high category, Image of urban destination in the high category, Post-visit behavior in the high category, and the influence of city branding on image of urban destination and it impact on post-visit tourist behavior to Bandung city by 33,1%.